Evaluation of Sysmex XN-1000 hematology analyzer for cell count and screening of malignant cells of serous cavity effusion. Issue 27 (July 2017) - Xu, Weiyi; Yu, Qian; Xie, Lixia; Chen, Baode; Zhang, Ling
Abstract : Abstract: Over the years, with the advancement in hematology analyzer technology, the use of fluid analysis method has seen a drastic increase in clinical examinations. Cell counting and classification in independent body fluid analysis method are conducted by semiconductor laser flow cytometry and nucleic acid fluorescence staining techniques. This study is to evaluate the efficacy of Sysmex XN-1000 hematology analyzer in cell counting and to screen malignant cells with serous cavity effusion. Specimens (N = 206) with serous cavity effusion from our hospital were included in this study. Manual and instrumental methods for cell counting, nucleated cell classification, and high-fluorescent cells (HFC) were used in this study. The correlation between RBC, nucleated cell count (NUC), the percentages of polymorphonuclear cell (PMN%), and mononuclear cells (MN%) was statistically analyzed using manual and instrumental methods. The regression equations of RBC, NUC, PMN%, and MN% in the manual and instrumental methods were RBC y = 0.88x + 426.4; NUC y = 0.85x + 33.4; PMN% y = 0.91x + 4.2; and MN% y = 0.91x + 5.1. Correlation coefficient R 2 was 0.99, 0.98, 0.90, and 0.90 ( P  < .001). ROC curve analysis showed that when the cut-off value of HFC% was 4.4% and HFC# was 24.5/μL, area under curve (AUC), sensitivity, specificity, and 95% confidence interval were 0.707, 0.792, 0.558, 0.637–0.777; 0.708, 0.753, 0.550, 0.635–0.780, respectively. XN-1000 hematology analyzer body fluid method can accurately and rapidly count cell and nucleated cell classification with serous cavity effusion. HFC can indicate the possible existence of malignant cells; however, further investigations are required to validate its efficacy.